2022
DOI: 10.1002/rmv.2412
|View full text |Cite
|
Sign up to set email alerts
|

Partners in crime: Autoantibodies complicit in COVID‐19 pathogenesis

Abstract: Autoantibodies (AABs) play a critical role in the pathogenesis of autoimmune diseases (AIDs) and serve as a diagnostic and prognostic tool in assessing these complex disorders. Viral infections have long been recognized as a principal environmental factor affecting the production of AABs and the development of autoimmunity. COVID‐19 has primarily been considered a hyperinflammatory syndrome triggered by a cytokine storm. In the following, the role of maladaptive B cell response and AABs became more apparent in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 122 publications
0
12
0
Order By: Relevance
“…The DNA in the neutrophil extracellular trap promotes the citrullination process that further ampli es the production of anti-CCP [28]. SARS-CoV-2 infection is a potent inducer of NETosis and citrullination, which leads to neoantigens that trigger the development of Anti-CCP (3). The anti-CCP can be detected in a median of 4.5 years before the development of RA phenotype (2).…”
Section: Analysis Between Variablesmentioning
confidence: 99%
See 3 more Smart Citations
“…The DNA in the neutrophil extracellular trap promotes the citrullination process that further ampli es the production of anti-CCP [28]. SARS-CoV-2 infection is a potent inducer of NETosis and citrullination, which leads to neoantigens that trigger the development of Anti-CCP (3). The anti-CCP can be detected in a median of 4.5 years before the development of RA phenotype (2).…”
Section: Analysis Between Variablesmentioning
confidence: 99%
“…Some antibodies like anti-CCP in rheumatoid arthritis become positive in the serum a median of 4.5 years before the initiation of clinical manifestation [2]. Viruses are among the most acknowledged environmental factor that elicits the production of AABs in systemic and organ-speci c autoimmune disorders [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6] Severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2), the viral agent of COVID-19, elicits the production of AABs through several mechanisms, including toll-like receptor (TLR) engagement, eliciting extrafollicular B cell response, cytokine storm, and neutrophil extracellular traps (NETs) formation. 3,6,7 Previous investigations, including studies conducted by Woodruff et al 7 and Anaya et al, 8 showed the production of AABs associated with rheumatologic disorders, especially systemic lupus erythematosus (SLE) in COVID-19, which was reviewed comprehensively by Taghadosi et al 3 Among several AABs reported in COVID-19 patients, the AABs associated with systemic autoimmune disorders, including antinuclear antibodies (ANAs) and antiphospholipid antibodies (aPLs), have an association with some clinical manifestations of COVID-19, including long-COVID, thrombosis, and venous occlusion. [9][10][11][12] The extent of antibody production in COVID-19 is enormous and the presence of COVID-19-specific AABs has implications in stratifying patients into specific disease phenotypes.…”
Section: Introductionmentioning
confidence: 99%